EC-CTA Fisheries Cooperation Bulletin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
C Nauen, Editor in Chief. EC Fisheries Cooperation Bulletin, DG VIII/D-5 Development Office Commission of the European Communities, 200 rue de la Loi 1049 Brussels, BELGIUM